A robust and representative lower bound on object processing speed in humans. (14th November 2015) - Bieniek, Magdalena M.; Bennett, Patrick J.; Sekuler, Allison B.; Rousselet, Guillaume A.
Abstract: How early does the brain decode object categories? Addressing this question is critical to constrain the type of neuronal architecture supporting object categorization. In this context, much effort has been devoted to estimating face processing speed. With onsets estimated from 50 to 150 ms, the timing of the first face‐sensitive responses in humans remains controversial. This controversy is due partially to the susceptibility of dynamic brain measurements to filtering distortions and analysis issues. Here, using distributions of single‐trial event‐related potentials (ERPs), causal filtering, statistical analyses at all electrodes and time points, and effective correction for multiple comparisons, we present evidence that the earliest categorical differences start around 90 ms following stimulus presentation. These results were obtained from a representative group of 120 participants, aged 18–81, who categorized images of faces and noise textures. The results were reliable across testing days, as determined by test–retest assessment in 74 of the participants. Furthermore, a control experiment showed similar ERP onsets for contrasts involving images of houses or white noise. Face onsets did not change with age, suggesting that face sensitivity occurs within 100 ms across the adult lifespan. Finally, the simplicity of the face–texture contrast, and the dominant midline distribution of the effects, suggest the face responses were evoked by relatively simple image properties and are not face specific. Our results provide a new lower benchmark for the earliest neuronal responses to complex objects in the human visual system. Abstract : Using event‐related potentials in a sample of 120 human participants aged 18–81, we found evidence for onsets of neuronal activity to images of objects within 100 ms. The results are reliable across testing days, independent of age, and not due to filtering distortions or lack of control for multiple comparisons. The results provide a new lower benchmark for the earliest neuronal responses to complex objects in the human visual system.